Sequencing the Iberian pig genomes - Esteve A.; Kofler R.; Himmelbauer H.; Groenen M.; Rodríguez M.C.; Pérez-Enciso M. (7th International Symposium on the Mediterranean Pig, 2012)
The Iberian pig is one of the most important varieties of local pig breeds, both economically and culturally. Contrary to most widespread breeds, like Duroc or Large White, it seems not to have been intercrossed with Chinese pigs. Modern sequencing technologies allow us to sequence and analyze complete genomes for costs in the order of a few thousand euros, democratizing the access to this kind of data. Here we present preliminary results of the partial sequencing a highly inbred animal of the Guadyerbas strain.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)